Genome-wide identification and functional characterization of inhibitor of nuclear factor-κB (IκB) kinase (IKK) in turbot (Scophthalmus maximus). Issue 134 (March 2023) - Liu, Zhe; Liu, Peng; Cui, Tong; Chen, Xuan; Wang, Beibei; Gao, Chengbin; Wang, Zhongyi; Li, Chao; Yang, Ning
Abstract: The inhibitor of nuclear factor-κB (IκB) kinase (IKK) is involved in a variety of intracellular cell signaling pathways and is an important component of the NF-κB signaling pathway. IKK genes have been suggested to play important roles in the innate immune response to pathogen infection in both vertebrates and invertebrates. However, little information is available about IKK genes in turbot ( Scophthalmus maximus ). In this study, six IKK genes were identified including SmIKKα, SmIKKα2, SmIKKβ, SmIKKε, SmIKKγ, and SmTBK1. The IKK genes of turbot showed the highest identity and similarity with Cynoglossus semilaevis . Then, phylogenetic analysis showed that the IKK genes of turbot were most closely related to C. semilaevis . In addition, IKK genes were widely expressed in all the examined tissues. Meanwhile, the expression patterns of IKK genes were investigated by QRT-PCR after Vibrio anguillarum and Aeromonas salmonicida infection. The results showed that IKK genes had varying expression patterns in mucosal tissues after bacteria infection, indicating that they may play key roles in maintaining the integrity of the mucosal barrier. Subsequently, protein and protein interaction (PPI) network analysis showed that most proteins interacting with IKK genes were located in the NF-κB signaling pathway. Finally, the double luciferase report and overexpression experiments showed that SmIKKα/SmIKKα2/SmIKKβ involved in the activation of NF-κB in turbot. In summary, our results suggested that IKK genes of turbot played important roles in the innate immune response of teleost, and provide valuable information for further study of the function of IKK genes. Highlights: Six IKK genes were identified including IKKα, IKKα2, IKKβ, IKKε, IKKγ, and TBK1. IKK genes had varying expression levels in mucosal tissues after bacteria infection. The double luciferase report and overexpression experiment showed that IKK genes were involved in the activation of NF-κB.